1966
DOI: 10.1071/ea9660432
|View full text |Cite
|
Sign up to set email alerts
|

The internal microflora of wheat grains in Western Australia

Abstract: The microflora of 568 samples of surface sterilized wheat grains, harvested in 1963-64 and 1964-65 in Western Australia, were examined. Alternaria spp, were the most commonly isolated organisms, being present in 17.7 per cent of all grain and 98.7 per cent of all samples over the two years. The frequency of occurrence was not related to grain discolouration. Of the remaining organisms, Helminthosporium sativum, Fusarium spp., Podosporiella vertillata, and Septoria nodorum are known to be pathogenic to wheat. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1971
1971
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…In contrast to the present study Shipton [27] found a rather high incidence of Cladosporium spp. in surface sterilized wheat grains but seed germination was not impaired by these fungi.…”
Section: Resultscontrasting
confidence: 83%
“…In contrast to the present study Shipton [27] found a rather high incidence of Cladosporium spp. in surface sterilized wheat grains but seed germination was not impaired by these fungi.…”
Section: Resultscontrasting
confidence: 83%
“…These results concur with Berghofer et al (2003) who detected Aureobasidium, Alternaria and Fusarium in Australian wheat. A similar study by Shipton and Chambers (1966) found Cladosporium, Rhizopus spp., Penicillium spp., Alternaria spp., Stemplium spp., and Ulocladium spp., associated with Western Australian wheat. In similar studies in Mediterranean environments Cladosporiumand Rhizopus species were isolated from wheat in Argentinia (González et al 1999), Aspergillus (mainly A. flavus, A. niger and A. versicolour) from wheat in Algeria (Riba et al 2008) and Cladosporium spp., Alternaria spp., Penicillium spp., Aspergillus spp.…”
Section: Discussionmentioning
confidence: 65%
“…Previous research also reported Altemaria spp. and C. sativus being present in symptomless wheat kernels (Agrawal et al, 1987;Conner and Kuzyk, 1988a;Cromey and Mulholland, 1988;Fernandez et al, 1994;Klein, 1987;Maloy and Specht, 1988;Rees et al, 1984;Shipton and Chambers, 1966). For germination, there was no difference among treatments, except for kernels from the CS treatment, which had a lower mean percentage germination than the other treatments, including ALT, regardless of whether the kernels were discolored or symptomless (Table 4).…”
Section: Fungal Isolations and Germination Of Discolored And Symptomlmentioning
confidence: 84%
“…Fungal inoculum was prepared by growing each isolate on potato dextrose agar. After incubating associated with fungal infection in common wheat (Ellis et al, 1996;Kaan et al, 1995;Shipton and Chambers, 1966). Walker et al (2008) suggested that environmental conditions at grain fi ll might be linked to the associated enzymatic browning process and BP formation in barley (Hordeum vulgare L.).…”
Section: Humidity and Fungal Treatments Under Two Temperature Regimesmentioning
confidence: 99%
See 1 more Smart Citation